Properties Of Silver-Filled Epoxy Composites For Electronic Application Using Synthesized And Commercial Silver Nanoparticles - Ghazali, Suriati (2012)
In this research, silver nanoparticles (SAgNPs) were synthesized by chemical reduction method while trisodium citrate and ascorbic acid were used as reducing agent and stabilizing agent, respectively. The effect of silver salt, reducing agent and stabilizing agent’s concentration were analyzed by TEM, SEM, EDX, XRD and UV-vis. Due to very low yield in obtaining SAgNP through synthesis route, composite sample was prepared in thin film form and compared with commercial silver; e.g. silver nanoparticles (CAgNPs) and silver flakes (CAgFs). The aims of this research are to study the effect of processing techniques, sizes and shapes of filler, hybrid between nano and micron size of Ag filler and filler treatment on electrical, mechanical,